Le problème de fidélité au texte folklorique et les contes traditionnels dans les recueils de Barbier et d’Azkue - Zaïka, Natalia M. (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2010)
The present article attempts to analyse the methods that were used in the transcription of the fairy-tales, as well as their accuracy, the research being based on some texts collected in the 19th and 20th centuries. I analysed the problem of the accuracy of folk text transcriptions in general, paying special attention to two Basque classical fairy-tale collections, that of R. M. de Azkue —Euskalerriaren Yakintza. Literatura popular del País Vaco II: Ipuin eta irakurgaiak [Azkue 1942], and that of J. Barbier —Légendes basques [Barbier 1931]. I concluded that Azkue’s collection is not original and I examined Azkue’s modifications. Having compared Barbier’s collection to that of J.-F. Cerquand, I elicited numerous coincidences between the texts, wich led me to conclude that Barbier’s book was influenced by Cerquand’s collection.